Analisis Pengenalan Konsep Algoritma Pemrograman Matematika Pada Kehidupan Sehari Hari - Ahmad Al-hafiz Sagala; Yahfizham Yahfizham (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Algorithms and programming play a crucial role in problem solving and software development. The origin of the word "algorithm" comes from "algorism," and its history can be traced to Abu Ja'far Muhammad Ibn Musa Al-khuwarizmi. This article presents definitions of algorithms from several sources, such as Kani (2020), Jando &; Nani (2018), Munir & Lidya (2016), and Sismoro (2005). The programming algorithm, as a series of logical and systematic steps, becomes the core in Troubleshooting. The research method applied is descriptive and qualitative, by collecting information from various sources, including books, journal articles, and research reports. The discussion in this article covers the significance of algorithms in everyday life and their application in computer programming. In addition, this article details the basic concepts of algorithms, the role of programming languages, and algorithm representation techniques. In the discussion section, it was revealed that algorithms involve logical and systematic steps to solve a task or problem. The basic structure of the algorithm includes repetition, branching, and sequential order. Programming languages contribute to simplifying human interaction with computers, increasing productivity, as well as facilitating software maintenance and development. Algorithms can be represented in the form of descriptive sentences, pseudocode, or flowcharts. Flowcharts use symbols to illustrate the steps of solving a problem. Repetition, branching, and sequential structures can be clearly described through flowcharts. This article provides a comprehensive overview of algorithms and programming, giving readers insight into the basic concepts, implementation, and importance of algorithms in the context of computer programming.